Flea weevils of the genus Megorchestes Kojima (Coleoptera, Curculionidae, Curculioninae, Rhamphini), with description of a second species from India - Ayri, Shaloo; Kojima, Hiroaki; Ramamurthy, V. V. (Zootaxa, 2014)
A second species of Megorchestes Kojima, M. deccanensis sp. nov., is described from India and a key to the two species is provided.